2010
DOI: 10.1007/s10329-010-0209-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of non-taster Japanese macaques for a specific bitter taste

Abstract: Bitter taste perception evolved as a key detection mechanism against the ingestion of bioactive substances, and is mediated by TAS2R gene family members in vertebrates. The most widely known and best studied bitter substance is phenylthiocarbamide (PTC), which is recognized by TAS2R38 and has a molecular structure similar to that of glucosinolates contained in Brassica plants. The "non-taster" phenotypic polymorphism (i.e., not sensitive to PTC-containing foods) has been identified in many primates, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…This phenotypic variation of PTC perception has been found in many primate taxa, and the causal gene was first identified as TAS2R38 in humans [37][40]. Different types of nonsense mutations in TAS2R38 orthologues and PTC inactivation in homozygous individuals were also found in Japanese macaques ( Macaca fuscata ) as types of intraspecific variation [41]. Similar to the occurrence of the non-functional allele of TAS2R38 about 0.5 mya in chimpanzees, phylogenetic analyses revealed that the non-functional allele of TAS2R38 arouse between 0.3–1.6 mya in humans and at around 0.5 mya in Japanese macaques [41], [42].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This phenotypic variation of PTC perception has been found in many primate taxa, and the causal gene was first identified as TAS2R38 in humans [37][40]. Different types of nonsense mutations in TAS2R38 orthologues and PTC inactivation in homozygous individuals were also found in Japanese macaques ( Macaca fuscata ) as types of intraspecific variation [41]. Similar to the occurrence of the non-functional allele of TAS2R38 about 0.5 mya in chimpanzees, phylogenetic analyses revealed that the non-functional allele of TAS2R38 arouse between 0.3–1.6 mya in humans and at around 0.5 mya in Japanese macaques [41], [42].…”
Section: Discussionmentioning
confidence: 84%
“…Different types of nonsense mutations in TAS2R38 orthologues and PTC inactivation in homozygous individuals were also found in Japanese macaques ( Macaca fuscata ) as types of intraspecific variation [41]. Similar to the occurrence of the non-functional allele of TAS2R38 about 0.5 mya in chimpanzees, phylogenetic analyses revealed that the non-functional allele of TAS2R38 arouse between 0.3–1.6 mya in humans and at around 0.5 mya in Japanese macaques [41], [42]. The occurrence of PTC non-tasters in multiple species may thus have resulted from similar selective pressure by a global alteration of climate and flora during the Pleistocene epoch, which was characterized by repeated global glaciations.…”
Section: Discussionmentioning
confidence: 90%
“…Another case of convergent evolution of taste was found in the Tas2r38 receptor gene. Mutations in the Tas2r38 gene have resulted in independent loss of phenylthiocarbamide sensitivity in some humans, chimpanzees, and macaques (30,31). Notably, the mutations in chimpanzees and macaques are start codon mutations, resembling the case with sea lion and fur seal Tas1r2s (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The less common variants of hTAS2R38, namely AAI, PVI, and AAV, show intermediate sensitivity to PTC (Bufe et al, ). Few studies of nonhuman primates have explored the functional divergence of TAS2R38 with respect to PTC sensitivity, including studies of Macaca fuscata and Pan troglodytes (Suzuki et al, ; Wooding et al, ).…”
Section: Introductionmentioning
confidence: 99%